2006
DOI: 10.1080/10920277.2006.10597420
|View full text |Cite
|
Sign up to set email alerts
|

Development and Pricing of a New Participating Contract

Abstract: The purpose of this article is to design and price a new type of participating life insurance contract. Participating contracts are popular in France, Denmark, the UK (where they are called with-profit contracts)... They satisfy various covenants and obey various regulations depending on the country where they are issued. The standard literature is Briys and de Varenne [1994, 1997a] and Grosen and Jørgensen [2000], to quote only a few. Bernard, Le Courtois and Quittard-Pinon [2005] study a particular type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Moody's credit rating, a small volatility of 10% leads to a very small default probability and this leads to an Aaa rating of the company, a volatility value of 15% results in Baa. 5 Thanks to its definition, one can easily see that the probability of default is a increasing function with respect to the variable η. The higher the η, the higher the default probability.…”
Section: Aim 1: Controlling the Default Probabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…Moody's credit rating, a small volatility of 10% leads to a very small default probability and this leads to an Aaa rating of the company, a volatility value of 15% results in Baa. 5 Thanks to its definition, one can easily see that the probability of default is a increasing function with respect to the variable η. The higher the η, the higher the default probability.…”
Section: Aim 1: Controlling the Default Probabilitymentioning
confidence: 98%
“…In addition, it is observed that a quite low regulation parameter η which results in a quite low barrier level should be chosen in order to keep the insurance company to at (or below) a reasonable default probability. 5 According to Moody's rating, for a 20-year horizon, the ratings and the respective default probabilities are given as follows: Aaa, 1.55%; Aa, 2.70%, A, 5.24% and Baa, 12.59%.…”
Section: Aim 1: Controlling the Default Probabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, it is easy to compute this value in closed form, even with stochastic interest rates, when it is assumed that default can occur only at maturity (see, e.g., Bernard et al 2006, the computation of [2.4], p. 182). To eliminate the stochastic discount factor, we move to the T-forward neutral universe.…”
Section: Market Modelmentioning
confidence: 99%
“…It is possible to compute the expectation E Q [ N T ] if the intensity model of N T is specified, while the second expectation can be developed in a closed or semiclosed form (see Bernard, Le Courtois, and Quittard‐Pinon 2006 for simple expressions of ). Next, we note that the following equality can be obtained easily: Therefore, we can express V 3 0 as follows: …”
Section: Valuation and Capital Structure Of The Firmmentioning
confidence: 99%